Penerapan Kearifan Lokal Dalam Mata Pelajaran Pendidikan Pancasila Dan Kewarganegaraan Kelas VIIB Di UPTD SMP Negeri 05 Bangkalan - Ilham; Dian Eka Indriani; Anindita Trinura Novitasari (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
This study is entitled "The Application of Local Wisdom in the Subjects of Pancasila Education and Class VII B Citizenship in UPTD SMP Negeri 05 Bangkalan". This type of research used in this study is a type of qualitative descriptive study, research in which problem solving procedures are investigated by describing or describing the state of the subject or object of research. This research was conducted in 1 of the 1 meetings, consisting of four stages, namely questionnaire, interview, observation and documentation. Questionnaire and interview data collection techniques. The results showed that the application of local wisdom in the PPKn was still being carried out in PPkn subjects at SMP Negeri 05 Bangkalan. This shows that in this globalization era, PPKn teachers still maintain local wisdom in PPKn subjects, such as praying, saying greetings, greetings, courtesy, mutual cooperation, and obeying discipline. Thus it can be concluded that by applying local wisdom in PPKn subjects can improve teacher skills, student activities, and teaching and learning in class VII B students of SMP Negeri 05 Bangkalan. The application of local wisdom can maintain local wisdom during the PPKn learning process. so that it can be applied to other subjects.